Oncogenic RAS drives the CRAF‐dependent extracellular vesicle uptake mechanism coupled with metastasis. Issue 8 (10th June 2021) - Choi, Dongsic; Montermini, Laura; Meehan, Brian; Lazaris, Anthoula; Metrakos, Peter; Rak, Janusz
Abstract: Oncogenic RAS impacts communication between cancer cells and their microenvironment, but it is unclear how this process influences cellular interactions with extracellular vesicles (EVs). This is important as intercellular EV trafficking plays a key role in cancer invasion and metastasis. Here we report that overexpression of mutant RAS drives the EV internalization switch from endocytosis (in non‐transformed cells) to macropinocytosis (in cancer cells) resulting in enhanced EV uptake. This process depends on the surface proteoglycan, fibronectin and EV engulfment mechanism regulated by CRAF. Both mutant RAS and activated CRAF expression is associated with formation of membrane ruffles to which they colocalize along with actin, sodium‐hydrogen exchangers (NHEs) and phosphorylated myosin phosphatase (pMYPT). RAS‐transformed cells internalize EVs in the vicinity of ruffled structures followed by apparent trafficking to lysosome and degradation. NHE inhibitor (EIPA) suppresses RAS‐driven EV uptake, along with adhesion‐independent clonal growth and experimental metastasis in mice. Thus, EV uptake may represent a targetable step in progression of RAS‐driven cancers.